Growth of Chlamydia psittaci in macrophages. - Wyrick, P B (1978)
Survival and growth of L-cell-cultivated Chlamydia psittaci occurred in mouse macrophages in vitro. Two major factors governing the intracellular fate of chlamydiae in macrophages are: (i) the multiplicity of infection (MOI), i.e., the elementary body (EB)-to-macrophage ratio, and (ii) the state of the EB. At a low MOI (1:1) survival and growth of live, untreated chlamydiae were optimal. The chlamydiae were internalized in macrophages within 30 to 40 min. EB proceeded to differentiate into reticulate bodies, which underwent multiplication and further matured into infectious EB in the professional phagocytic cells. In contrast, at a high MOI (100:1), survival of untreated chlamydiae was greatly reduced as a result of immediate damage to the macrophages. eb that were pretreated with heat (56 degrees C for 10 to 30 min) or coated with homologous antibody were rapidly destroyed in macrophage phagolysosomes. Fusion of ferritin-labeled lysosomes with heat-treated or opsonized EB-laden phagosomes occurred in 2 to 4 h, resulting in transfer of the ferritin marker into phagolysosomes.